Somatostatin receptor ligands induce TSH deficiency in thyrotropin-secreting pituitary adenoma. Issue 1 (January 2021) - Illouz, Frédéric; Chanson, Philippe; Sonnet, Emmanuel; Brue, Thierry; Ferriere, Amandine; Raffin Sanson, Marie-Laure; Vantyghem, Marie-Christine; Raverot, Gérald; Munier, Mathilde; Rodien, Patrice; Briet, Claire
Abstract : Objective: Somatostatin receptor ligands (SRL) are useful to control central hyperthyroidism in patients with thyrotropin-secreting pituitary adenoma (TSH pituitary adenoma). The aim of this study was to describe the frequency of thyrotropin deficiency (TSH deficiency) in patients with TSH pituitary adenoma treated by SRL. Design: Retrospective study. Methods: Patients with central hyperthyroidism due to TSH pituitary adenoma treated by short or long-acting SRL were retrospectively included. TSH deficiency was defined by a low FT4 associated with non-elevated TSH concentrations during SRL therapy. We analysed the frequency of TSH deficiency and the characteristics of patients with or without TSH deficiency. Results: Forty-six patients were included. SRL were used as the first-line therapy in 21 of 46 patients (46%). Central hyperthyroidism was controlled in 36 of 46 patients (78%). TSH deficiency appeared in 7 of 46 patients (15%) after a median time of 4 weeks (4–7) and for a median duration of 3 months (2.5–3). The TSH deficiency occurred after one to three injections of long-acting SRL used as first-line therapy in 6/7 cases. There were no differences in terms of clinical and hormonal features, size of adenomas or doses of SRL between patients with or without TSH deficiency. Conclusions: SRL can induce TSH deficiency in patients with central hyperthyroidism due to TSH pituitary adenoma. Thyrotropic function should be assessed before the first three injections of SRL in order to track TSH deficiency and reduce the frequency of injections when control of thyrotoxicosis rather than tumour reduction is the aim of the treatment.